Corrosion inhibition of mild steel in hydrochloric acid solutions by the extract of nypa fruticans wurmb - Muhammad Saiful Azreen, Ismail (2015)
This study assesses the corrosion inhibition effect of the leaves of Nypa Fruticans Wurmb on the corrosion of mild steel in hydrochloric acid medium. The inhibition performance of this natural corrosion inhibitor was determined in certain condition. The inhibitor was prepared by extraction of Nypa Fruticans leaves and the solutions was prepared according to different concentration of the inhibitor and concentration of HCl. Weight loss study on mild steel was performed in order to find the inhibition efficiency (I.E%). Result from this study shows that the inhibition performance of Nypa Fruticans Wurmb is high at high concentration of the inhibitor. However, the concentration of HCl solution did not influence the inhibition efficiency. Nypa Fruticans inhibitor has great potential to be use in industries related with piping system as a clean, safe, and economic corrosion inhibitor